Implementing Differentiated Instruction Approach in Physical Training and Sports Lesson - Özbal, Ayşe; Sağlam, Mustafa; Cavkaytar, Serap (Turkish Education Association, 2019)
Since this study aims to test the applicability of differentiated instruction approach in 5th grade Physical Training and Sports lessons, it was designed as an action research. The study was conducted as part of 5th grade Physical Training and Sports lessons. The application was carried out as a whole class activity; however, the data obtained from 8 focus students was analyzed in more detail. The research used “centers” and “stations” strategies of “differentiated instruction”. The qualitative data of the study was collected through “video recordings”, “reflective journals”, “learner diaries” and “semi-structured interviews”; and quantitative data by administering the “Physical Training Course Attitude Scale”. The quantitative data was analyzed by using “SPSS for Windows 22”, and qualitative data through descriptive analysis. The qualitative analyses revealed that there was a significant increase in the post-test scores of students regarding their attitudes towards “physical education and sports course” when compared to pre-test scores. In addition, the data showed that students actively participated in the lessons, practiced more moves, socialized and developed the habit of working in teams, learned how to study independently and obeyed classroom rules.   In addition, there was a considerable increase in the cases of interaction among students, and they were more aware of their responsibilities. The students also developed a positive attitude towards showing respect to individual differences. Finally, the use of both product and process evaluation methods created positive results, and process evaluations made valuable contributions to the planning of the following lessons.The study concluded that it is possible to implement differentiated learning and organize this teaching process by applying a variety of strategies.
Keywords: Physical education and sports; "Stations" strategy; Differentiated instruction; "Centers" strategy; Action research; 4. Education